1987
DOI: 10.3382/ps.0660725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Addition of Vegetable Oil or Animal Tallow to Broiler Diets Containing Cassava Root Meal

Abstract: Two experiments were carried out to evaluate the effects on broiler performance of increasing by 5% the metabolizable energy level of diets containing cassava (Manihot esculenta Crantz) root meal (CRM: 0, 20, and 30%) by adding either vegetable oil (Experiment 1) or animal tallow (Experiment 2). The CRM used was detoxified by sun-drying whole root chips of a high cyanide-containing (bitter) cultivar (CMC-84) on a concrete floor. All experimental diets were supplied in mash form. Supplementary vegetable oil or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…The study showed that although the addition of cyanide to rice depressed growth, the cyanogenic glucoside of gari appeared to have no effect on growth. This is in agreement with the findings of Gomez et al (1987) in broilers, Radwan et al (1989) in rabbits and Zinn & De Peters (1992) in feed-lot cattle. Koskelo et al (1990) found that because muscle wasting was accompanied by simultaneous increase of adipose tissue, relative body weight did not decrease in children with newly diagnosed acute leukaemia, and therefore did not reveal the nutritional protein depletion that existed.…”
Section: Digestibility O F Cassava a N D Its Effect O N Growthsupporting
confidence: 93%
See 1 more Smart Citation
“…The study showed that although the addition of cyanide to rice depressed growth, the cyanogenic glucoside of gari appeared to have no effect on growth. This is in agreement with the findings of Gomez et al (1987) in broilers, Radwan et al (1989) in rabbits and Zinn & De Peters (1992) in feed-lot cattle. Koskelo et al (1990) found that because muscle wasting was accompanied by simultaneous increase of adipose tissue, relative body weight did not decrease in children with newly diagnosed acute leukaemia, and therefore did not reveal the nutritional protein depletion that existed.…”
Section: Digestibility O F Cassava a N D Its Effect O N Growthsupporting
confidence: 93%
“…The study showed that although the addition of cyanide to rice depressed growth, the cyanogenic glucoside of gari appeared to have no effect on growth. This is in agreement with the findings of Gomez et al (1987) (1990) found that because muscle wasting was accompanied by simultaneous increase of adipose tissue, relative body weight did not decrease in children with newly diagnosed acute leukaemia, and therefore did not reveal the nutritional protein depletion that existed. This resembles the finding in the gari-fed dogs that mean weekly percentage change in weight did not differ from that of the rice-fed dogs, even though the serum albumin concentration was significantly lower.…”
Section: Digestibility O F Cassava a N D Its Effect O N Growthsupporting
confidence: 81%
“…The maximum recommended level of cassava meal that can be used in broiler diets varies greatly among studies. Osei and Duodu (1988) stated the recommended level should be 10% and Gomez et al. (1987) recommended 30%, but De Brum et al.…”
Section: Nutritive Value Of Cassava For Broilersmentioning
confidence: 99%
“…Hebert and Cerniglia (1981) reported that male broiler chicks performed better on soya bean oil-containing diets, whereas females performed better on animal tallow-containing diets. Gomez et al (1987) did not observe any differences in broiler performance between diets containing animal tallow or vegetable oil. Mossab et al (2000) reported that young chickens at 1Á3 wk of age were more efficient for soya oil diets compared with animal tallow, but at 3 wk of age an increase was observed in fat utilisation.…”
Section: K Karimi and A Ebadimentioning
confidence: 45%